Otonomi Dalam Kepemimpinan Sekolah: Peluang, Tantangan, Dan Dampaknya Bagi Sekolah - Alya, Nur Alya Fadilla Ismail; Nurul Annisa R; Sri Hastuti (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2025)
Educational autonomy grants schools greater authority to independently manage resources, policies, and operations as a result of post-reform education decentralization. This study aims to analyze the forms of autonomy within school leadership, the opportunities and challenges that arise, and their impact on educational quality. The method employed is a systematic literature review by examining studies from the last five years related to educational autonomy, school leadership autonomy, and education decentralization. The findings indicate that autonomy enables schools to be more adaptive to local needs through flexible curriculum management, human resource management, and financial administration. The success of autonomy implementation is strongly influenced by the principal’s leadership competence, particularly transformational leadership that fosters innovation, participation, and collaboration among school members. However, obstacles such as resource disparities, limited managerial capacity, regional budget constraints, and low community involvement remain major challenges. Overall, educational autonomy has the potential to improve school quality when supported by strong leadership, clear regulations, and adequate resource readiness.